Ijtihad Jama'i, Multi, Inter, and Transdisciplinary Approaches: A New Paradigm of Contemporary Islamic Law - Khuluq, M. Khusnul; Mu’allim, Amir; Mukharrom, Tamyiz (International Journal of Science and Society, 2024)
This article discusses the concept and application of ijtihad jama'i in the context of contemporary Islamic law. The dynamics and complexities of contemporary Islamic law require a new paradigm to obtain a comprehensive understanding of an issue. In complex issues, individual ijtihad with a mono-disciplinary approach is no longer able to provide a comprehensive picture. This article uses a qualitative approach, utilizing relevant literature as a source. Ijtihad jama'i, which is a collective effort to formulate solutions relevant to the dynamics of modern society, is examined. Meanwhile, multidisciplinarity, interdisciplinarity, and transdisciplinarity represent new approaches in formulating Islamic law today. These approaches allow for collaboration and integration across various disciplines. In practice, the success of ijtihad jama'i in meeting the demands of modern society requires collaboration between scholars, legal practitioners, and experts from various disciplines. With this new paradigm, Islamic law on any given issue can be formulated more comprehensively. Thus, this article provides in-depth insight into how ijtihad jama'i, with multidisciplinarity, interdisciplinarity, and transdisciplinarity approaches, can become a new paradigm in addressing the challenges of Islamic law in the contemporary era.